The Effect of Acid Activated Natural Zeolite Catalyst on Further Catalytic Cracking of Liquid Product’s Heavy Fraction from Plastic Waste Treatment Factory - D. Darwanta; Zakarias Faidiban; Frans A. Asmuruf (Indonesian Journal of Chemistry and Environment, 2021)
The influence of activated natural zeolite catalyst on the further cracking of liquid product’s heavy fraction from plastic waste treatment factory been studied resulting in alternative fuel oil. Natural zeolite from Wonosari, Yogyakarta was activated with 1 M H2SO4 solution. Natural zeolite and activated zeolite were characterized using XRD at an angle of 2ϴ=5-60 degrees. Further cracking process was carried out to study the ratio of catalyst mass of 25 g; 50 g; 75 g; 100 g to 750 mL weight fraction of the factory liquid product. The further cracking product was flame tested, specific gravity measured by gravimetric method and characterized using GC-MS. The calculation of the constituent fuel fractions is also carried out. The performance test of the further cracking product as an alternative fuel was carried out for the generator engine ignition process. The result showed that the activation process using acid was not destroy the zeolite structure. The study of ratio catalyst to liquid waste volume obtained an optimum result at 50 g/750 mL based on the volume of resulted fuel oil with small amount of catalyst. The resulted fuel oil has a density of 0.7908 g/mL with a clear yellow color, and flammable. The GC-MS analysis resulted in fuel oil consisting of 4.11% gasoline, 8.42 kerosene, 75.56% solar, and 11.93% heavy fraction